Changes in practice and organisation surrounding blood transfusion in NHS trusts in England 1995–2005. Issue 4 (4th August 2008) - Taylor, C J C; Murphy, M F; Lowe, D; Pearson, M
Abstract : Background: Between 1996 and 2005 in the UK, the Serious Hazards of Transfusion (SHOT) scheme has reported 105 deaths and 296 patients developing major morbidity due to transfusion. Accurate patient identification and monitoring of patients during blood transfusion are vital in ensuring patient safety, and national guidelines have been in place since 1999. There have been numerous initiatives in the UK in recent years promoting safe and appropriate use of blood and this paper reports the results of the 2005 National Comparative Audit of transfusion practice, and compares this audit with previous audits and survey results. Methods: The 2005 audit consisted of two parts looking at organisational factors and bedside practice. To enable comparison with previous audits and surveys the 2005 data have been limited to English NHS sites (217 sites for organisational, 211 sites for bedside practice). Results: Hospital transfusion committees were well established by 2003 though hospital transfusion teams have lagged behind. 86% of hospitals reported having established teams by 2005 although only 52% reported having all essential elements of the team in place. Only 38% reported having trained at least half of their nurses in blood transfusion. Bedside practice has improved, although in 2005, 6% of patients receiving a blood transfusion had no identification wristband in place, and in 9% of those who did, the details were incomplete. Observation of vital signs during transfusions has also improved, although in 2005, 13% of patients receiving a transfusion had had no observations recorded. Conclusion: This paper document the progress that has been made in the UK in establishing an effective infrastructure for the support of safe transfusion practice, and the measurable improvements in bedside transfusion practice. There remain, however, many areas of poor practice, and the improvements have not been seen across all hospitals. It is still too early to say whether progress made is being translated into a reduction in serious transfusion errors at the bedside. Further progress needs to be made.